Purchase Decision: As A Mediation Variable of Digital Marketing Relations, Product Design, Product Quality on Consumer Satisfaction - Nadya Nur Arifa; Deykha Aguilika (PT Mattawang Mediatama Solution, 2023)
This study aims to determine purchase decision as a mediation variable of digital marketing relations, product design, product quality on consumer satisfaction with Mete Sultan products. The sample used was Mete Sultan consumers with certain criteria. This research is quantitative in nature, the sample was taken using non probability sampling technique using purposive sampling. This study uses instrument development consisting of a validation test and also a reliability test which is applied to test each statement number in the questionnaire. In this study, the data analysis techniques chosen were regression analysis and mediation test. The results of this study indicate a positive and significant effect of digital marketing and product quality on purchasing decisions. However, product design has no positive and significant effect on purchasing decisions. Purchasing decisions have a positive and significant effect on customer satisfaction. Purchasing decisions are able to mediate digital marketing and product design on customer satisfaction. However, purchasing decisions do not successfully mediate product quality on customer satisfaction.